Nivel de conocimiento, actitudes y prácticas sobre prevención y control del dengue en estudiantes, Facultad de Farmacia y Bioquímica-UNAP, 2023 - Crispin Alvear, David Jonathan (2024)
INTRODUCTION: Dengue is the most widely transmitted viral disease by insects worldwide, causing symptoms that range from none to severe systemic illness or "breakbone" fever. Recently, a high number of cases have been reported in our region and generally in our country. OBJECTIVE: The purpose of this study was to determine the level of knowledge, attitudes, and practices regarding dengue prevention and control strategies to facilitate and promote prevention processes that contribute to minimizing and mitigating its effects among students. METHODOLOGY: A descriptive, prospective, and cross-sectional study was conducted. The quantitative approach was implemented through a survey administered to students. The study population consisted of 257 students enrolled from 1st to 5th levels. Sample: 149 students selected by random sampling. The data obtained were processed using a statistical program and Microsoft Excel 2019. RESULTS: The students' level of knowledge is good, with an 80.6% cumulative percentage. Regarding attitudes and practices, this research found that 87.3% of the students have favorable and satisfactory attitudes and practices. CONCLUSIONS: The level of knowledge among the students was good in more than 60% of the respondents. Regarding attitudes and practices, it was found that they are favorable and satisfactory in more than 55% of the students.